What's the difference? - coaching female and male handball players - Marczinka, Z. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
In today`s society, there is parity between the sexes. In handball, the rules and competition schedule are the same for both men and women, so too is the technical and tactical repertoire required of the two genders. It is logical then, to assume that men and women teams are prepared in the same manner. However, experience has proven that due to the anthropometrical, hormonal, psychological, social, emotional and sexual differences developed through evolution, female and male players (thus men and women`s teams) require different approaches from the coach. I have been fortunate to have worked with both genders at both national and club level. In my article, I collate and summarise the differences between the two genders by looking at four major aspects of training. • PHYSICAL ABILITIES - differences in: strength, agility, endurance, flexibility, body mass, proportion of muscle and fat, proportion of trunk and limbs • CO-ORDINATIONAL ABILITIES - differences in: special awareness, eye/limb and eye/ball coordination, movement coordination • COGNITIVE ABILITIES - differences in: thought processes, visual perception, oral ability, communication skill, learning style, personality • EMOTIONAL FACTORS - differences in: social relationships, behaviour on and off court, emotional life, pain threshold, mood swings